The conservative uses of law: The Catholic mobilization against gender ideology - Vaggione, Juan Marco (2020)
The term ‘gender ideology’ has become a conceptual and political tool used by various religious and secular actors who defend a legal system embedded in a sexual universal morality. Although the use of the term began within the Catholic sphere, it currently characterizes the politics of different countries that are facing a wave of neoconservative activism. The article analyzes the expansion and uses of this term by considering two main aspects: first, an analysis of its emergence as a strategy by the Vatican to combat the impact of Sexual and Reproductive Rights (SRR) on Universal Human Rights; second, a presentation of the appropriations and uses of the fight against gender ideology as part of a neoconservative movement in Latin America.